2008
DOI: 10.1177/082585970802400403
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Scale Assessing Spiritual Needs for Korean Patients with Cancer

Abstract: The purpose of this study was to develop a scale assessing the spiritual needs of Korean patients with cancer. For the scale development, qualitative interviews and theoretical analyses were conducted to extract measurable constructs within the Korean culture. As a result, 26 items were developed for the validation of a scale. The scale was administered to 257 cancer patients; the reliability and validity of the scale were examined using Cronbach's alpha and factor analysis, respectively. The reliability was 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 37 publications
0
52
0
3
Order By: Relevance
“…Compared to the five dimensions of the Spiritual Needs Scale (SNS) of Yong et al [32] (Table 5), we have similar dimensions, albeit with different weightings, but lack the scale 'acceptance of dying'; this topic was addressed with the single items N12 (talk with someone about the possibility of life after death) and N5 (dissolve open aspects of your life) of the Existentialistic Needs scale. Due to strong side loadings, the items dealing with the topic of Forgiveness were eliminated from the item pool; nevertheless, item N17 (to be forgiven) can be used as a marker item.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Compared to the five dimensions of the Spiritual Needs Scale (SNS) of Yong et al [32] (Table 5), we have similar dimensions, albeit with different weightings, but lack the scale 'acceptance of dying'; this topic was addressed with the single items N12 (talk with someone about the possibility of life after death) and N5 (dissolve open aspects of your life) of the Existentialistic Needs scale. Due to strong side loadings, the items dealing with the topic of Forgiveness were eliminated from the item pool; nevertheless, item N17 (to be forgiven) can be used as a marker item.…”
Section: Discussionmentioning
confidence: 93%
“…Enrolling cancer patients in hospice home care, it became evident a that spiritual needs may exhibit a great variability; among these needs, family was the most frequently cited one (80%); attending religious services was the most frequently cited unmet need [25]. In Korean patients with cancer, Yong et al identified 5 sub-constructs of spiritual needs [32], i.e., love and connection, hope and peace, meaning and purpose, relationship with God, and acceptance of dying.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this review was not limited to English-language instruments, but also included some measures initially developed in French, German, and Korean. 51,71,75 In conclusion, this systematic review provides detailed information on instruments to assess the complex relationship between spirituality and health. Results demonstrate the relative scarcity of instruments specifically designed to measure a patient's current spiritual state.…”
Section: Discussionmentioning
confidence: 98%
“…Twenty-two instruments were classified as measures of general spirituality. 20,37-64 These instruments [73][74][75][76] .…”
Section: Ovid Medlinementioning
confidence: 99%
“…A systematic review published in 2011 reports 35 instruments validated for the assessment of spirituality and four with the concept of need of spirituality: Spiritual Need Inventory (SNI) - assessed for patients near the end of life, Spiritual Interests Related to Illness Tool (SpIRIT) - developed for patients and family members, Spiritual Needs Scale (SNS) - Korean questionnaire with 26 items validated by Yong et al [6], and the Spiritual Needs Questionnaire (SpQN) - developed for patients with chronic diseases [7]. Another systematic revision of spirituality questionnaires in the Portuguese language shows the existence of 20 instruments, 15 of which are translated from other languages, but without the different instruments of spiritual need [8].…”
Section: Introductionmentioning
confidence: 99%